The Effect of Pandemic Shocks on the Performance of Middle Eastern and African Firms: How Did the Debt Strategy Shape This Effect? - Elnady, Farah Medhat (AUC Knowledge Fountain, 2024)
This paper studies the impact of the Covid-19 pandemic on financial services firms operating in Middle Eastern and African (“MEA”) countries. The methodology utilized firm-level data from MEA countries, employing the panel regression techniques using fixed and random effects models to control for the potential omitted variable bias. The results of the study underlay that (1) With every 1% increase in new Covid-19 cases market capitalization for firms operating within financial services in MEA countries decreases by 0.11%. (2) Highly indebted financial services firms are more responsive to the Covid-19 pandemic, while low debt firms happen to be more resilient against external shocks (3) The monetary policy impact on corporate performance is more pronounced for firms with high debt levels, compared to firms with low debt levels. In this paper the researcher contributes to the growing literature by assessing how financial services firms operating in MEA countries are impacted by external shocks, namely the Covid-19 pandemic, shedding light on the difference in responses between firms with different debt strategies. Second, the paper provides a framework to be used by policy makers to understand and deal with the ramifications posed by a pandemic on firms operating within the financial services sector.